The Learning Innovation Skills of Vocational Teacher Candidates: A Case Study in the Vocational Education Program of Mechanical Engineering at Untirta - Nana Suryana; Sulaeman Deni Ramdani; Deddy Supriyatna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore learning innovation skills in vocational teacher candidates in the Mechanical Engineering Vocational Education Program (PVTM) at Sultan Ageng Tirtayasa University. A qualitative approach with a case study method was used in this research. Data were collected through observations and in-depth interviews, utilizing interview guides and assessment rubrics to ensure the objectivity of the analysis. The research sample was drawn from 30% of students previously categorized as having low skills based on earlier studies, with the condition that they had completed the School Field Introduction course (PLP). The results showed that this classification was not entirely accurate. Some students categorized as “low” actually demonstrated strong competencies in innovative skills such as creative thinking, collaboration, communication, and problem-solving. The findings suggest that PVTM students have potential that can be developed into adaptive vocational teachers who are capable of facing the challenges of 21st-century learning. Strengthening teaching strategies and holistic evaluations is crucial to optimizing their abilities.